The Synthesis and Biological Evaluation of a Novel Pleuromutilin Derivative Containing a 4-Fluorophenyl Group Targeting MRSA - Yongfei Wang; Yi Zhao; Haiting Wang; Bo Liu; Shuangyi Zhang; Yuan Liu; Ruinan Li; Tao Zhang; Surong Hasi; Wei Mao (Molecules)
The pleuromutilin derivative, the compound PL-W, was synthesized by introducing a 4-fluorophenyl group at the C21 position and selected for comprehensive antibacterial evaluation. PL-W demonstrated notable antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA), with a minimum inhibitory concentration (MIC) of 0.03125 µg/mL, which is significantly lower than that of tiamulin (0.5 µg/mL). Crystal violet (CV) staining revealed that it inhibited MRSA biofilm formation and electron microscopy revealed that it disrupted bacterial cell division and, possibly, the synthesis of essential cell wall proteins. In both in vivo models, PL-W exhibited excellent performance. In the Galleria mellonella infection model, treatment with different concentrations of PL-W increased the survival rate from 20% to 90% and significantly reduced the bacterial load. In the mouse model of MRSA pneumonia, a 10 mg/kg dose of PL-W increased the survival rate to 70%, decreased the bacterial load in the lungs, and alleviated inflammatory damage. Molecular docking studies indicated that PL-W had a similar docking pose and comparable binding affinity to that of lefamulin, with hydrogen bond interactions that are crucial for binding to the peptidyl transferase center (PTC). Moreover, it demonstrated no significant reduction in cell viability in HepG2 and HEK293 cells, even at high concentrations (≤50 µg/mL). Overall, PL-W shows significant potential as a novel anti-MRSA agent owing to its potent in vitro and in vivo activities and low cytotoxicity.